Covariate-adjusted response adaptive designs incorporating covariates with and without treatment interactions - Zhu, Hongjian (Canadian journal of statistics, 2015)
The covariate-adjusted response adaptive (CARA) design has been shown to be better than traditional designs in terms of both ethics and efficiency. However, its mechanism for allocating subjects makes certain stochastic processes such as allocated response sequences very complicated. Consequently, the validation of statistical inference is usually challenging, and few theoretical results have been obtained. In this paper we systematically solve some fundamental problems for statistical inference with CARA designs. First, we obtain the conditional independence and distribution of allocated response sequences, which is the basis for further theoretical investigation. Second, we propose a new family of CARA designs, which is extensively applicable. We more importantly provide a framework for new CARA designs with unified asymptotic results for statistical inference. The numerical results demonstrate the advantages of the proposed CARA designs. Our findings are crucial in understanding the CARA design as well as its development and application. La supériorité des plans d'expérience adaptatifs dont la réponse est ajustée par des covariables (ARAC) a été démontrée tant au plan de l'éthique que de l'efficacité. Les mécanismes d'attribution des sujets rendent toutefois très complexes les processus stochastiques comme les séquences de réponses attribuées. Par conséquent, la validation de l'inférence statistique est un véritable défi et peu de résultats théoriques ont été obtenus. L'auteur aborde de façon systématique quelques problèmes liés aux plans ARAC et les résout. Il montre d'abord l'indépendance conditionnelle des séquences de réponses attribuées et détermine leur distribution, ce qui le mène à d'autres problèmes théoriques. Il propose alors une nouvelle famille de plans ARAC largement applicables et développe un cadre dans lequel il élabore une théorie asymptotique unifiée pour l'inférence statistique. L'auteur présente des résultats numériques démontrant l'avantage des plans ARAC proposés. Ces conclusions permettent une meilleure compréhension des plans ARAC et contribuent à leur développement et à leur utilisation.